(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the 1950’s America, the literary movement that came to be known as The Beat Generation discarded customary narrative ethics and materialism, explored spiritual quest in their own way and experimented with promiscuous relations and psychedelic drugs. The Beats were of the generation who grew up in the destructive shadow of the Second World War and spent most of their youth in a post-war disenchanted environment. The term ‘beat generation’ was first used by Jack Kerouac in conversation with writer John Clellon Holmes in 1948. The group of writers that was indulged in Beat Generation was very cynical and iconoclasts by nature and believed in spontaneity in prose and poetry writing. This paper is an attempt to look out at the spiritual quest and the psychological conflict of reaching out at the ultimate truth by acquiring a way that was much foreign to the materialist West in the novel The Dharma Bums. What is the ultimate truth? What is the way out of life’s sufferings? What is the purpose we dwell here for? And finally what is the purpose of all this existence that is going on and on from eternity to time without end? These are some of the questions that happen to come in the mind of every thinking being but our focus is post-Second World War youth of America who had gone profligate and revolutionary as the result of huge destruction brought up by the war.